Penyuluhan Cara Mencegah Obesitas Pada Remaja dengan Pola Makan Yang Sehat - Rosyda Dianah; Endah Ayu Andari; Elvira Anjani Putri; Cahya Chita Dwinanti; Diassyifa Naqwa Nafisah (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
Indonesian teenagers are currently facing nutritional problems, one of it is obesity that will be serious problem because it will continue into adult. The long-term effects of obesity are respiratory problems, joint disorders and increases risk of degenerative diseases (hypertension, diabetes mellitus, heart disease). One of the causes of obesity in teenagers is wrong eating habits, including preferring junk food, packaged food and drinks, and lack consumption of fruit and vegetables. The aim of this activity is provides education about the importance of implementing a healthy diet to prevent obesity among teenagers. This counseling is carried out by lecturers and students of the Food Service and Nutrition Industry Management, IPB Vocational School, online via zoom, attended by 1 teacher and 47 students at SMP PGRI 5 Bogor. The stages of the activity are filling out the pre-test, presenting the material, implementing games, filling out the post-test. The results of the counseling show that the post-test results have increased compared to the pre-test results of 7.3% so it can be concluded that there has been an increase in the cognitive of the counseling participants about implementing a healthy diet to prevent obesity and is expected to help reduce the incidence of obesity with providing an interesting knowledge about obesity in an interesting and clear way to resolve that problem, how to deal with obesity properly and correctly, and how to live with healthy diet and healthy lifestyle.